Enhancing walking efficiency of adolescents with neurological impairments using an exosuit for ambulatory activities of daily living - Basla, Chiara; Mariani, Giulia; Wolf, Peter; Riener, Robert; van Hedel, Hubertus J. A. (Frontiers in Robotics and AI, 2024)
Introduction Children and adolescents with neurological impairments face reduced participation and independence in daily life activities due to walking difficulties. Existing assistive devices often offer insufficient support, potentially leading to wheelchair dependence and limiting physical activity and daily life engagement. Mobile wearable robots, such as exoskeletons and exosuits, have shown promise in supporting adults during activities of daily living but are underexplored for children. Methods We conducted a cross-sectional study to examine the potential of a cable-driven exosuit, the Myosuit, to enhance walking efficiency in adolescents with diverse ambulatory impairments. Each participant walked a course including up-hill, down-hill, level ground walking, and stairs ascending and descending, with and without the exosuit’s assistance. We monitored the time and step count to complete the course and the average heart rate and muscle activity. Additionally, we assessed the adolescents' perspective on the exosuit’s utility using a visual analog scale. Results Six adolescents completed the study. Although not statistically significant, five participants completed the course with the exosuit’s assistance in reduced time (time reduction range: [-3.87, 17.42]%, p-value: 0.08, effect size: 0.88). The number of steps taken decreased significantly with the Myosuit’s assistance (steps reduction range: [1.07, 15.71]%, p-value: 0.04, effect size: 0.90). Heart rate and muscle activity did not differ between Myosuit-assisted and unassisted conditions (p-value: 0.96 and 0.35, effect size: 0.02 and 0.42, respectively). Participants generally perceived reduced effort and increased safety with the Myosuit’s assistance, especially during tasks involving concentric contractions (e.g., walking uphill). Three participants expressed a willingness to use the Myosuit in daily life, while the others found it heavy or too conspicuous. Discussion Increased walking speed without increasing physical effort when performing activities of daily living could lead to higher levels of participation and increased functional independence. Despite perceiving the benefits introduced by the exosuit’s assistance, adolescents reported the need for further modification of the device design before using it extensively at home and in the community.